Evidence of wildfire in the British Isles during the Last Glacial-Interglacial Transition: Revealing spatiotemporal patterns and controls. Issue 5 (October 2020) - Tsakiridou, Margarita; Hardiman, Mark; Grant, Michael J.; Lincoln, Paul C.; Cunningham, Laura
Abstract: Charcoal records are now widely used to reconstruct past burning activity as there is an increasing global interest in understanding the complex interactions between fire, climate, vegetation and human activity. However, this topic has been relatively overlooked in the British Isles, as the region is generally thought to not support natural burning regimes. Here, for the first time, we present a synthesis of previously published charcoal data for 238 sites and demonstrate the widespread occurrence of charcoal in sediments that span the Last Glacial-Interglacial Transition (LGIT; c. 17−8.3 ka cal. BP) in the British Isles. Analysis is based upon a semi-quantitative analysis of the assembled dataset; the common patterns are identified and are considered in relation to independent reconstructions of climate, vegetation and anthropogenic activity. No causal relationships with vegetation are identified, while charcoal is also prominent during periods when archaeological evidence for human occupation of the British Isles is absent or scarce. Climate is very likely to have controlled the fire regimes during the LGIT. We conclude with ten research priorities to further advance our understanding of palaeofire drivers during the Lateglacial-Early Holocene.